Effects of the Jigsaw method on student educational outcomes: systematic review and meta-analyses - Cochon Drouet, Océane; Lentillon-Kaestner, Vanessa; Margas, Nicolas (Frontiers in Psychology, 2023)
Introduction Cooperative learning methods are particularly interesting for building more inclusive schools; however, they have not been widely implemented. Among cooperative learning methods, the Jigsaw strategy is attractive for teachers, as it seems to be easy to implement and follow its four-step teaching structure; in addition, this method is believed to improve students' socialization and learning. To identify the effects of the Jigsaw method accurately, a systematic review of studies that have tested the effects of this method on important student educational outcomes was proposed and completed using a meta-analytical approach. Methods A total of 69 Jigsaw studies were analyzed, and three major outcomes were retained following inductive and deductive thematic analyses: learning (including achievement and motivation), social relations, and self- esteem (including academic self-esteem and social self-esteem). When possible, complementary meta-analyses were conducted to quantify the Jigsaw effects on achievement (n = 43), motivation (n = 5), social relations (n = 4), and academic self-esteem (n = 4). Results The primary results of our review focused on the inconsistency of Jigsaw effects and the high degree of variability among studies with regard to all retained student educational outcomes (i.e., achievement, motivation, social relations, and academic self-esteem) with the exception of social self-esteem, for which only three studies concluded that the Jigsaw method had positive effects. Moreover, homogeneous results were observed within studies. Our review highlights several factors that may explain this variability among studies: the sample size, the diversity of students in the classroom, and the type of content taught. Discussion The moderating roles of these factors must be tested empirically, as they suggest ways of implementing the Jigsaw method more efficiently.